A Secondary Study on Green Marketing in India: The Emerging Opportunities and Challenges - Rajveer Singh (Journal of Advanced Research in Journalism & Mass Communication, 2024)
Green marketing has gained significant attention in recent years as businesses and consumers have become increasingly aware of environmental issues and the need for sustainable practices. This study examines the emerging opportunities and challenges of green marketing in India, a country experiencing rapid economic growth and environmental concerns. The paper provides a comprehensive analysis of the current state of green marketing in India, focusing on the opportunities it presents for businesses operating in various sectors. These opportunities include the growing demand for eco-friendly products and services, the rise of environmentally conscious consumers, and the potential for cost savings through sustainable practices. Additionally, the study highlights the role of government regulations and initiatives in promoting green marketing in the country. However, along with these opportunities, several challenges exist for businesses engaging in green marketing in India. These challenges encompass issues such as lack of awareness and understanding of green products, price sensitivity, inconsistent consumer behaviour, and the need for effective communication strategies. Furthermore, the paper discusses the complexities associated with green certifications, labelling, and standards, which can pose obstacles for businesses aiming to establish their eco-friendly credentials. To navigate these opportunities and challenges, businesses need to adopt innovative marketing strategies that effectively communicate the environmental benefits of their products and services to consumers. The study emphasizes the importance of educating consumers, enhancing consumer trust through transparency, and fostering collaborations among stakeholders in order to promote sustainable consumption patterns. Overall, this research sheds light on the emerging opportunities and challenges of green marketing in India. It provides valuable insights for businesses, policymakers, and researchers, serving as a guide to harness the potential of green marketing in India's dynamic and environmentally conscious market. By understanding and addressing these opportunities and challenges, businesses can align their marketing efforts with sustainability objectives, contributing to a greener and more sustainable future.